2002
DOI: 10.1103/physrevlett.89.257201
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Second-Order Transverse Magnetic Anisotropy inMn12-Acetate

Abstract: The symmetry breaking effects for quantum tunneling of the magnetization in Mn12-acetate, a molecular nanomagnet, represent an open problem. We present structural evidence that the disorder of the acetic acid of crystallization induces sizable distortion of the Mn(III) sites, giving rise to six different isomers. Four isomers have symmetry lower than tetragonal and a nonzero second-order transverse magnetic anisotropy, which has been evaluated using a ligand field approach. The result of the calculation leads … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
207
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(232 citation statements)
references
References 23 publications
21
207
1
3
Order By: Relevance
“…[20]). Furthermore, we have seen these extra peaks in all of the samples that we have studied, as have Barra et al [10] and Cornia et al [23]. There do, however, appear to be noticeable differences in the positions and intensities of anomalous EPR peaks obtained by different groups.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…[20]). Furthermore, we have seen these extra peaks in all of the samples that we have studied, as have Barra et al [10] and Cornia et al [23]. There do, however, appear to be noticeable differences in the positions and intensities of anomalous EPR peaks obtained by different groups.…”
Section: Introductionsupporting
confidence: 70%
“…One particular proposal considers long-range strains caused by dislocations [19,20]. However, a more likely scenario involves acetate ligand disorder which would give rise to distinct Mn 12 Á/Ac isomers with local site symmetry lower than S 4 [7,12,17,23]. Indeed, recent experiments clearly show that a narrow distribution of tunnel splittings exists [7], a fact which is consistent with the ligand disorder scenario.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Magnetic tunneling measurements, however, showed that some of the resonant tunneling occurred at a level lower than fourth order. 2 To understand this anomaly in the tunneling, Cornia et al 7 proposed that inherent disorder in solvent molecules may break the S 4 symmetry and provide nonzero values of E. Recent electron paramagnetic resonance (EPR) experiments 8,9 and magnetic tunneling measurements 9,10 revealed that the model of Cornia et al 7 needed to be refined for a quantitative comparison with experiment. Our DF calculations 6 on the Mn 12 showed that the values of E for possible configurations of the disordered solvent molecules are in good quantitative agreement with experiment.…”
mentioning
confidence: 99%
“…13,18 The imperfections in large complex molecules such as Mn 12 could be of many types, such as dislocations 7 and the disorder caused by the various orientations of the acetate ligand and of the solvent molecules in a unit cell. 8 So far the origin of the possible defects has not yet been clarified. In the study, 13,14 we modeled that the defects could be represented by the distributions in the uniaxial anisotropy parameter D (second-order anisotropy) and the g-factor.…”
Section: Introductionmentioning
confidence: 99%